Provence and the British Imagination - A cura di: Claire Davison (Ledizioni, 2013)
Although it resonates today with lavender fields, sunny heritage locations and the gentrified memory of Paul Cézanne's pictorial turbulence, Provence has not always been the attractive territory of pacified leisure and festival culture. Since the seventeenth century, indeed, the region has inscribed its shifting geography, complex politics and the extraordinary diversity of its land and seascapes in the perception and imagination of British visitors.